Reconstructing the temperature degree of the warm seasons through Quercus persica tree rings in Zagros forests Dena region - Hossein zarean (تحقیقات کاربردی علوم جغرافیایی)
Trees can record long-term effects of climate variables. Using dendroclimatology knowledge, we can reconstruct such variables especially for areas which have short-term climatic data. For this purpose, we reconstructed the temperature degree of the warm months (May-September) through annual rings width of Quercus persica and regression analysis of data obtained from stations on Dena region. With this goal in mind, three growth heights were selected in Dena Forests and 52 growth samples from 26 bases were extracted and their growth rings width were measured with LINTAB5 with an accuracy of 0.01 mm. After cross dating stage, to eliminate non-climate effects, May to September temperature average and tree rings time series were standardized. The Residual Chronology (RES) calculated by ARSTAN was calibrated with temperature degree of the period 1882-2011 and its positive and significant correlation with the width of growth rings was confirmed. Based on the relations between the calculated chronology and joint statistical temperature degree data, the reconstruction of temperature degree of the warm seasons for over a century was performed and it was found that in the last three decades, region's average temperature of May to September had an increase in comparison to the average of the previous century.